DOHaD in science and society: emergent opportunities and novel responsibilities. (23rd November 2018) - Penkler, M.; Hanson, M.; Biesma, R.; Müller, R.
Abstract: The field of Developmental Origins of Health and Disease (DOHaD) has grown considerably in recent decades and is receiving increasing recognition from health policymakers. Today, DOHaD research aims to offer a comprehensive perspective on health and disease that traces how different life experiences shape health and disease risks over the entire life course. This integrative perspective opens up distinct possibilities for improving health. At the same time, it raises questions regarding the specific social responsibilities of DOHaD as a field and about possible pathways to a socially just and scientifically robust implementation of DOHaD knowledge in society. In this article, we review the history and key characteristics of DOHaD as a field of scientific knowledge production. We argue that based on its key assumptions – that life circumstances, health and disease are closely linked on a molecular scale – DOHaD is an inherently political research field. When tracing how life environments affect health and disease, it is of utmost social and political importance to specify how DOHaD understands and frames these life environments, which aspects of life worlds are included and which excluded, and how research results are interpreted and translated into health recommendations at individual, societal and policy levels. We suggest a number of ways by which the DOHaD community can constructively and responsibly meet the demands that these inherent characteristics place on knowledge production and dissemination in the field.